Determinación del remanente natural del cantón Saquisilí, provincia de Cotopaxí. - Villavicencio Villarroel, Jessica Paulina (2017)
The investigation project determined the Natural Remnant existing in of the highlands Saquisilí town, taking as reference the areas of the intervened highlands. Data and information were gathered about the highlands by carrying out field visits to the parishes of Canchagua and Cochapamba, using methodology proposed by the authors Sarmiento and León(2015), linear transects of 500 meters as sample units, with methodology of Halffter and Moreno (2015); it was also possible to determine the indexes of Flower Diversity, and with the methodology established by the Amazon Institute of Scientific Investigation of Colombia-SINCHI.(2000); the index of Remnant Vegetation. The obtained results were as following: Index of Remnant Vegetation (IVR) 16,35% (category 10-LOW), Indexes of Flower Diversity: 1) Total Combined Richness, 2) Number of Unique Species in 2 Sides (UAB): 29species, 3) Fulfillment of the Biotic (CAAB): 0,41….,when comparing with the classification chart of vegetable coverage by the intervention of the institute SINCHI(2000), it was possible to determine that Ecosystem of the Highlands of Saquisilí Town are classified in the category of transformation 4: Completely Transformed, since its natural vegetation represents only the 26,35% of the total area, this is due to the incidence of factors such as the development of agricultural borders, deforestation, human settlement and cattle, which have an increasing tendency without the inhabitants of such town become conscious of this problem and search for alternatives for its solution. Key Words: Remnant, qualitative, ecosystems, highlands, Saquisilí, vegetable coverage, IVR, Index of Remnant Vegetation, geo-reference, flora, natural, Index of Flower Diversity.